Large deformation mechanism of thin-layered carbonaceous slate and energy coupling support technology of NPR anchor cable in Minxian Tunnel: A case study. (November 2021) - Wang, F.N.; Guo, Z.B.; Qiao, X.B.; Fan, J.Y.; Li, W.; Mi, M.; Tao, Z.G.; He, M.C.
Highlights: High geo-stress and soft rock mass are main reasons of large deformation in tunnel. NPR anchor cable keeps constant resistance 350 kN and adapts to large deformation. Energy absorbed by NPR anchor cables should been greater than releasing by rock mass. The release of energy of the primary support ensures the safety of secondary lining. NPR anchor cable can solve the large deformation and failure in soft rock tunnel. Abstract: To solve the large deformation problem of thin-layered carbonaceous slate in Minxian Tunnel, the mechanical properties and large-deformation mechanism of carbonaceous slate are analyzed. A negative Poisson's ratio (NPR) anchor cable supporting solution was designed based on the principle of energy coupling support and field tests were carried out. Thin-layered low-strength jointed rock mass and extremely high geo-stress is found to be the main causes of large deformation in Minxian Tunnel. Dissolution of clay minerals in carbonaceous slate by fissure water accelerates softening of surrounding rocks, which is another reason for the large deformation. The adopted NPR anchor cable energy supporting system can maintain a constant support reaction force (350 ± 10kN) for the surrounding rock, releasing the deformation energy of the surrounding rock through conical body sliding. Evaluation study on NPR anchor cable support was performed including axial force of NPR anchor cable, convergence deformation of surrounding rock, pressure monitoring between steel arch with surrounding rock and pressure monitoring between primary support structure with secondary lining. Monitoring results demonstrate the effectiveness of the adopted NPR anchor cable (7.3 m and 12.3 m) supporting system in Minxian Tunnel. This report would be helpful for the construction of soft rock tunnel under high geo-stress conditions for the control of large deformation and failure.